The link between labor cost and price inflation in the euro area - Elena Bobeica; Matteo Ciccarelli; Isabel Vansteenkiste (European Central Bank (ECB), 2019)
This paper documents, for the first time in a systematic manner, the link between labor cost and price inflation in the euro area. Using country and sector quarterly data over the period 1985Q1-2018Q1 we find a strong link between labor cost and price inflation in the four major economies of the euro area and across the three main sectors. The dynamic interaction between prices and wages is time-varying and depends on the state of the economy and on the shocks hitting the economy. Our results show that it is more likely that labor costs are passed on to price inflation with demand shocks than with supply shocks. However, the pass-through is systematically lower in periods of low inflation as compared to periods of high inflation. These results confirm that, under circumstances of predominantly demand shocks, labor cost increases will be passed on to prices. Coming from a period of low inflation, however, this pass-through could be moderate at least until inflation stably reaches a sustained path.
Keywords: C32; E24; E31; 330; Inflation; pass-through; labor costs; structural VAR; euro area